Systemic nodular panniculitis with cardiac involvement - Wilkinson, P. J. (1974)
A case of systemic nodular panniculitis is described in which the myocardium was found at necropsy to be extensively involved with focal interstitial carditis, identical histologically with nodules of panniculitis biopsied from the skin. This degree of myocardial involvement, which was not apparent during life and was not confined to pericardial or myocardial adipose tissue, has not previously been reported. The literature relating to nodular panniculitis is briefly reviewed and the concept of Weber-Christian disease critically re-appraised.